The complete mitogenome of a South African cryptic species of tadpole shrimp within the Triops granarius (Lucas, 1864) species group. Issue 1 (2nd January 2019) - Gan, Han Ming; John Wasserman, Ryan; Dalu, Tatenda; Christopher Rogers, D.
Abstract: The complete mitochondrial genome of a cryptic species of tadpole shrimp from South Africa (Accession Number: MG770893) was recovered by low coverage shotgun sequencing. The mitogenome consists of 15, 216 bp with a GC content of 30.95%. COX1 sequence alignment indicates that this specimen is the most closely related to Triops granarius with a pairwise nucleotide identity of less than 90% (86.6%). Phylogenetic analysis using whole mitogenome dataset supports its affiliation to the genus Triops with moderate support for its relatively basal position within the clade.